Influence of power generation period on the oily sludge bio-electrical system. (2nd February 2023) - Zeyu, Zhong; Guo, Haiying; Huang, Chunfeng; Geng, Xiaoheng; Jia, Xinlei; Huo, Hongjun; Li, Fanru; Jianfei, Gao
Abstract: The single-chamber bio-electrical systems can degrade oily sludge in sediments while generating electricity from the microbial fuel cells (MFCs) and their characteristics in energy and environmental effects have attracted wide international attention in recent years. To explore the influence of the power generation period on the oily sludge bio-electrical system, an oily sludge bio-electrical system was constructed. The output voltage, polarization curve, power density curve, crude oil removal rate and microflora were detected during different power generation periods, respectively. The results of this study showed that under the stable power generation period, the power generation and oily sludge degradation performance of MFC are higher than the voltage rise period and voltage attenuation period. Besides, the oily sludge bio-electrical system during the stable period contained more electricity-producing bacteria than the other two periods. The voltage in the stable period of oily sludge bio-electrical system is about 280 mV, the electromotive force is 493.1 mV and the power density is 134.93 mW·m −3 . It lays a foundation for the improvement of degradation of crude oil and power generation performance in oily sludge bio-electrical system. HIGHLIGHTS: We explore the influence of power generation periods on the performance of oily sludge SMFC. Oily sludge SMFC can effectively degrade crude oil and convert it into electricity. Power generation, oil degradation performance and bacterial community morphology, diversity, bacterial composition and relative abundance of oily sludge SMFC during different power generation periods were systematically compared. Graphical Abstract